Implementasi Kebijakan Desa Budaya Dalam Melestarikan Budaya Lokal Di Desa Sendangmulyo, Minggir, Sleman. - T Prasetyo Atmoko (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2018)
Local cultural values in cultural interaction cause people tend to ignore the values of local culture so that requires a policy in preserving local culture in the village Sendangmulyo, Minggir, Sleman. The purpose of this study is to know the potential of Sendangmulyo village and how the implementation of village culture policy in preserving local culture in Sendangmulyo village, Minggir, Sleman. This research method using descriptive qualitative research method. Based on research, Sendangmulyo village has cultural potential such as tabuh gamelan, dance art, Jathilan and Encling, Thek-Thek, Gejog Lesung, kethoprak, craft and culinary, and merti desa. Implementation of cultural village policy based on the assessment of the Culture Department of Yogyakarta, Sendangmulyo is in the category of advanced cultural village. The power factor of Sendangmulyo village is the cultural potential and the support of the community. Weakness of less skilled human resources, institutional lack of understanding of its function, as well as inadequate facilities become weaknesses, as well as understanding the culture and involvement of young people who are still less a threat factor. Opportunities that can be developed that Sendangmulyo village can be a cultural destination. In overcoming the weaknesses of human resources, institutions and facilities and infrastructure in Sendangmulyo village, the village government with the support of the Provincial Cultural Office of Yogyakarta Specialized by increasing the motivation, knowledge and participation of the community through trainings, improving village management institutions through increased management, village culture and provide funding to hold a cultural title